2015
DOI: 10.1111/bjh.13327
|View full text |Cite
|
Sign up to set email alerts
|

Management and controversies of classical Hodgkin lymphoma in pregnancy

Abstract: SummaryThe goal of managing classical Hodgkin lymphoma (cHL) in pregnancy is to obtain good long-term outcomes for both the mother and fetus. Given the excellent outcomes outside of pregnancy, the goal of treatment should remain curative. There remains a tension and debate regarding the timing of chemotherapy, the curative nature of such treatment and the timing of delivery. Moreover, the aim during pregnancy should be to minimize fetal toxicity and optimize perinatal outcomes. The management of cHL within pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 120 publications
1
21
0
1
Order By: Relevance
“…Table 2 show the clinical characteristics of newborns, the 4 newborns that received chemotherapy during the first trimester had low-weight: 1950 to 2100 (median: 2010) g, these fetuses began ABVD regimen at 12, 13, 16, and 16 weeks of pregnancy, but, all recovered the normal weight at a median of 7.4 weeks. 3 10 No congenital abnormalities were observed. Psychological, physical, neurological and cardiac tests were normal.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Table 2 show the clinical characteristics of newborns, the 4 newborns that received chemotherapy during the first trimester had low-weight: 1950 to 2100 (median: 2010) g, these fetuses began ABVD regimen at 12, 13, 16, and 16 weeks of pregnancy, but, all recovered the normal weight at a median of 7.4 weeks. 3 10 No congenital abnormalities were observed. Psychological, physical, neurological and cardiac tests were normal.…”
Section: Resultsmentioning
confidence: 96%
“…Treatment of advanced stages (IIB, III and IV) during pregnancy has well defined, and ABVD (adriamycin, bleomycin, vinblastine, and dacarbazine) is considered the best therapeutic option, with a very good response and overall survival, and minimal toxicity to the fetus, 4 11 even administered during the first trimester. 12 However, treatment during early stages (IA and IIA) remain controversial, while some oncologist suggested that chemotherapy administration will be deferred until after delivery, 4 6 , 8 10 and suggested that the use of single agent: vinblastine, could be administered, but, no precise schedule; dose, timing, time; has been considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with previous reports, our practice is to consider AT during the second and third trimesters if deferring that therapy until after delivery would be expected to compromise maternal outcome. 3,8,9 Figure. Progression-Free and Overall Survival Radiation therapy was given during pregnancy to four patients.…”
Section: Discussionmentioning
confidence: 99%
“…protocol remains the current treatment for HL in pregnancy in North America and Europe [13,14]. Small case series and retrospective studies in pregnancies treated for HL reported that doxorubicin was safe for the fetal heart when administered during the second and third trimester [9,12,[15][16][17]. But they reported that doxorubicin in pregnancy could reduce the thickness of the left ventricular wall without causing heart defects or functional disorders [15].…”
mentioning
confidence: 99%